CHAQ2020 - Seymour Island - Photographic data - CHAQ2020 - Seymour Island - Orthophotos - Westin, Jonathan; Almevik, Gunnar (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney.

After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903.

CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020.

This catalogue entry collects the photographic material and the panoramas from Seymour Island.

At the Argentinian Base Marambio a part of a wooden boat originating from the first Swedish South Polar Expedition is stored. It was found by Ricardo Capdevila in the 1980's at the south shore of Seymour Island and first brought to Snow Hill Island. At the time, the boat had parts of a ground stock connecting both sides of the clinker built planking. Today only one side of the planking is preserved. The full length of the remains is 4.8 meters and the two orthophotos have a resolution of 1mm per pixel.

The raw data used for the orthophotos is not available at the moment.

Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön.

Denna katalogpost samlar fotografier och panoraman från Seymourön.

Se den engelska beskrivningen för mer information.

På den argentinska basen Marambio förvaras en del av en träbåt med ursprung från den första svenska sydpolsexpeditionen. Resterna hittades av Ricardo Capdevila på 1980-talet på södra stranden av Seymourön och fördes först till Snow Hillön. Resternas fulla längd är 4,8 meter och de två ortofotona har en upplösning på 1 mm per pixel.

Rådatan för ortofotona finns för närvarande inte med i datasetet.
CHAQ2020 - Seymourön - Fotografiska data - CHAQ2020 - Seymourön - Ortofoton
Keywords: Antarctica; Antarktis; Antarctic region; archaeological site; arkeologiskt område; polar expeditions; polarexpeditioner; Nordenskjöld, Otto, 1869-1928; Nordenskjöld, Otto, 1869-1928; Swedish Antarctic Expedition, 1901-1904; Första svenska Antarktisexpeditionen, 1901-1904; History and Archaeology; Historia och arkeologi